Effect of Smoking on Ratio of K, Na, Ca, P & CL of Baghdad City Smokers - Nahlah F. Makki (Journal of Global Pharma Technology, 2018)
In this present paper  ,the effect of cigarette smoking for several years ranging from 5 to 30 years on the levels of K,NA, CA,P and CL in blood of smokers were  performed   by  C 4000 Auto analyzer .Two hundred of samples  were included  in this study , hundred specimen as a control group (non-smoking ),mean age 37 years  and other hundred as smokers group mean age 38 years  . The results elucidated that the ratio of Ca, P and CL   were not affected by smoking while sodium ions decrease in the serum of smokers compared to non-smokers and found that potassium ions are increasing at normal rates, it was also not found relationship between the period of smoking and the concentration of elements.  Therefore, you must avoid smoking, causing a change in the normal rates of essential elements of the body sodium and potassium and thus change in the work of hormones related to those elements Such as the hormone aldosterone, which leads to the occurrence of various diseases such as kidneys and stomach.Keywords: Cigarette, smoking, sodium, potassium.